2022
DOI: 10.47740/620.udsijd6i
|View full text |Cite
|
Sign up to set email alerts
|

Succession Management in Public Universities in Ghana: Context, Prospects and Success Factors - A Review of Literature

Abstract: Ghana, a sub-Saharan African country has been noted to be among the countries with a high rate of unemployment. An insight into the current trends in succession management in public institutions provides a panoramic view of the context, prospects, and success factors in the implementation of succession management in public universities in Ghana. As a country with a high unemployment rate coupled with a high rate of corruption and poverty, succession management has been found to be a challenging issue for unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Contrary to this SP recognition as a viable resource for effective leadership development and organizational performance, Graham (2018) has reported that NED firms risk folding up due to SP non-practice. Only recently, Wonnia (2021) reviewed literature on current trends in succession management of public universities in Ghana and concluded that the Ghanaian public universities did not follow routine procedures when replacing departing university officials. At the same time, new officials recruited or promoted through other non-SP procedure were found to have inadequate KSAs to effectively deliver on the job.…”
Section: Leadership Development and Organizational Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to this SP recognition as a viable resource for effective leadership development and organizational performance, Graham (2018) has reported that NED firms risk folding up due to SP non-practice. Only recently, Wonnia (2021) reviewed literature on current trends in succession management of public universities in Ghana and concluded that the Ghanaian public universities did not follow routine procedures when replacing departing university officials. At the same time, new officials recruited or promoted through other non-SP procedure were found to have inadequate KSAs to effectively deliver on the job.…”
Section: Leadership Development and Organizational Performancementioning
confidence: 99%
“…It was also estimated that, while some departmental heads may have received some SP training in the course of their duty, it was possible that any of the selected secretaries may have been present either as substantive or acting recorders of meetings where SP decisions were taken and that these secretaries may be willing to share their experiences with the researchers. Besides, Wonnia (2021) has advised that SP planning, execution and evaluation is a system-wide imperative and should not be viewed only as a senior management responsibility. On this score, it was appropriate to include middle management staff in the study.…”
Section: Sampling Techniquementioning
confidence: 99%
See 1 more Smart Citation